Three Months-Old’ Preferences for Biological Motion Configuration and Its Subsequent Decline - Lisboa, Isabel C. (2022)
Funding: ICL was supported by the Portuguese Science and Technology Foundation (PD/BD/105966/ 2014), and AFP by the research grants PTDC/PSI-GER/2463/2021, PTDC/MHC-PCN/1530/2014, and IF/ 00217/2013. This study was conducted at the Psychology Research Centre (PSI/01662), School of Psychology, University of Minho, supported by the Foundation for Science and Technology (FCT) through the Portuguese State Budget (Ref.: UIDB/PSI/01662/ 2020). Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.